Rainfall/runoff hydrological modeling using satellite precipitation information - Paul Hernández-Romero; Carlos Patiño-Gómez; Polioptro F. Martínez-Austria; Benito Corona-Vásquez (Water Practice and Technology, 2022)
The development of a rainfall/runoff hydrological model requires information regarding precipitation and different physical parameters. In Mexico, the availability of reliable and adequate meteorological information is currently troublesome. For instance, in some areas of the country, an adequate amount of information is available, but it is unreliable in quality; however, in other areas, few weather stations are established. An alternative to obtaining up-to-date satellite records is the CHRIPS database from the CLIMATESERV project, included in the SERVIR GLOBAL product catalog. The objective of this work is to present a comparative analysis and results of the rainfall/runoff process simulation performed through the HEC-HMS program while considering the Rio-Conchos basin as the study area. For the generation of the precipitation time series, the ERIC III and CHIRPS databases were used. The CLIMATESERV statistical assessments of the model showed a good performance with respect to on-site information. HIGHLIGHTS The hydrological modeling achieved in this research, incorporating a GIS system, is a tool for hydrological management.; This hydrological model is helping to improve water management.; The construction of a hydrological model requires reliable information, used in this research.; The results from the model were very good, and the calibration process also.; The validation process was very good based on the calibrated model.;